2020
DOI: 10.1097/md.0000000000021215
|View full text |Cite
|
Sign up to set email alerts
|

Penile metastasis in rectal cancer with pathologic complete response after neoadjuvant chemoradiotherapy

Abstract: Rationale: Penile metastasis in rectal cancer is very rare and often originates from prostatic or bladder cancer. The prognosis of penile metastasis is poor and its treatments are more often palliative than curative due to association with disseminated metastases. Pathologic complete response (pCR) in rectal cancer with neoadjuvant chemoradiotherapy (CRT) has been shown to be surrogate marker of favorable long-term outcomes and currently has no report of penile metastasis. Here, we first report is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Metastases can present as plaques, wart-like nodules, ulceration, erythema, or induration of the penis ( 5 ). The mass ordinarily progresses to involve the corpora cavernosa with extension into the neighboring perineal subcutaneous tissue, the corpus spongiosum, and bulb ( 6 ). Although pain is not the patient’s initial symptom, it is often the most prominent symptom in the later stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metastases can present as plaques, wart-like nodules, ulceration, erythema, or induration of the penis ( 5 ). The mass ordinarily progresses to involve the corpora cavernosa with extension into the neighboring perineal subcutaneous tissue, the corpus spongiosum, and bulb ( 6 ). Although pain is not the patient’s initial symptom, it is often the most prominent symptom in the later stage.…”
Section: Discussionmentioning
confidence: 99%
“…A patient underwent palliative chemotherapy treatment and still alive 4 months after diagnosis of penile metastases ( 5 ). Lee et al reported a patient with metastatic carcinoma from the rectal cancer and the patient was still alive after receiving palliative chemotherapy with modified FOLFOX-6 (mFOLFOX-6; oxaliplatin with 5-fluorouracil and folinic acid) plus bevacizumab ( 6 ). On average, penile metastasis from rectal adenocarcinoma can occur within 2 years after the diagnosis of the primary tumor ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…As this entity is very rare, there are no international or national treatment guidelines. Possible treatment modalities alone or in combinations include local excision of the tumor, total penectomy, chemotherapy, radiotherapy, and palliative treatment only ( 14 , 39 , 50 , 67 , 69 ). In our review, chemotherapy (alone or in combination with radiotherapy or surgical treatment) was the most often suggested treatment.…”
Section: Discussionmentioning
confidence: 99%